A Body of Knowledge: Somatic and Environmental Impacts in the Educational Encounter. (2nd January 2018) - Barrow, Giles
Abstract: The author explores the somatic experience in educational encounters and considers several associated themes, including the importance of space, landscape, and environment. Examples are provided to illustrate the impact of bodily experience on the learning process in addition to material featuring educational work outdoors. Further consideration is given to ecopsychological theory and specifically the integration of human and nonhuman dynamics. Final thoughts are offered regarding implications for the training and certification of transactional analysts.